The The Effect of Locally-Generated Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund on Capital Expenditure of Regencies and Municipalities in Indonesia - Haq, A'am Ikhwanul; Masdar, Rahma; Ikbal A, M; Betty (E-Jurnal Akuntansi, 2025)
This study aims to analyze the influence of regional revenue components namely Local Own-Source Revenue (PAD), the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and Revenue Sharing Funds (DBH) on capital expenditure in regency and city governments across Indonesia for the period 2017–2020. The research uses a sample of 503 local governments and relies on secondary data obtained from the Regional Revenue and Expenditure Realization Reports (APBD) published by the Ministry of Finance. The data were analyzed using multiple linear regression. The results indicate that all components of regional revenue PAD, DAU, DAK, and DBH have a positive effect on capital expenditure. This finding suggests that the greater the fiscal capacity of local governments, the greater their ability to allocate funds for public investment, such as infrastructure, social facilities, and public service amenities. In other words, stronger regional revenue not only expands fiscal space but also reflects the commitment of local governments to strengthening long-term development through capital spending.